Histopathological pattern of central nervous system tumor: A three year retrospective study (Journal of Pathology of Nepal, 2011)
Background: There is no documented data regarding the histopathological spectrum of the central nervous system (CNS) tumors in Nepal. The aim of this study was to establish the relative frequency of biopsy proven tumors of the CNS from a single university hospital in Nepal. Materials and Methods: In the period between1998-2000, we retrospectively analyzed data on 57 patients (28 male and 29 female) diagnosed with CNS tumors according to the World Health Organization’s diagnostic criteria. Patient data were retrieved from the archives of the department of Pathology, Nepal Medical College. Results: A total of 57 CNS tumors were diagnosed during a three year period. Of these, 49 (86%) were primary, and 8 (14%) were metastatic. The most frequent type of CNS tumors was astrocytoma (22 cases, 38.6%), followed by meningioma (8 cases, 14%) and metastatic tumor (8 cases, 14%). Among the 8 metastatic tumors, the most common histologic type was adenocarcinoma (7 cases, 87.5%). Conclusion: The most frequent type of CNS tumors in this study was astrocytoma, followed by meningioma and metastatic tumor. The ratio of male to female for all CNS tumors was 0.9:1. Female outnumbered male in meningioma (1:0.3). Keywords: Astrocytoma; Meningioma; Tumor; Nepal; Central nervous system   DOI: 10.3126/jpn.v1i1.4445 Journal of Pathology of Nepal (2011) Vol.1, 22-25